Sebaran Salinitas Pada Saat IOD Positif Tahun 2019 di Perairan Provinsi Bengkulu - Septi Johan; Supiyati Supiyati; Suwarsono Suwarsono (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2023)
This study aims to look at the distribution of salinity in the waters of Bengkulu Province during the strong positive IOD events that occurred in 2019. The research area is the Bengkulu Province region which is in position a using in-depth zonal current data, in-depth temperature data and salinity data. To see the distribution map, this data is then processed using GrADS (The Grid Analysis and Display System) software. The analysis used in this study is the Hӧvmuller diagram analysis. Based on the results of the study during a positive IOD it was seen that there was a movement of deep zonal currents. These zonal currents carry low-temperature water masses from the deep layers to the surface layers. Prior to the occurrence of a positive IOD, the salinity value in Bengkulu Province waters varied between . When a positive IOD occurs, the salinity value in Bengkulu Province waters rises to and is almost uniform.